FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI JAGUNG DI KECAMATAN TANJUNG RAYA KABUPATEN AGAM - Rendi Rahma Perdana; Idris Idris; Alpon Satrianto (Jurnal Ecogen, 2018)
This study aims to examine (1) the effect of capital on the income of sweet corn farmers in Tanjung Raya District, Agam Regency (2) Effect of farming experience on the income of sweet corn farmers in Tanjung Raya District, Agam Regency (3) Effect of education level on income of sweet corn farmers in Tanjung Raya District, Agam Regency. (4) Effect of capital, farming experience and education level on the income of sweet corn farmers in Tanjung Raya District, Agam Regency. This type of research is classified as quantitative research. The population of this study is sweet corn farmers in Tanjung Raya sub-district, Agam district. The sample was determined based on the total sampling method, as many as 50 respondents. Data was collected by distributing questionnaires directly to the respondents concerned. Data analysis techniques using multiple linear regression with t test and F test. he results showed that (1) Capital has a positive and significant effect on the income of sweet corn farmers in Tanjung Raya District, Agam Regency (sig 0,000 <α = 0.05) with a magnitude of 19,164% (2) Farming experience has a positive and not significant effect on income Sweet corn farmers in Tanjung Raya District, Agam Regency (sig 0.360> α = 0.05) with a large influence of 0.923% (3) The level of education has a positive and insignificant effect on the income of sweet corn farmers in Tanjung Raya District, Agam Regency (sig 0.2333 > α = 0.05) with a magnitude of effect of 1.207%. Capital, farming experience and education level, together have a significant effect on the income of sweet corn farmers in Tanjung Raya District, Agam Regency (sig 0,000 at the level of α = 0.05) with the results of the analysis obtained Fcount 159.98> Ftable 2,807. Based on the results of the study, it is advisable for sweet corn farmers to increase the amount of capital and increase knowledge related to maize cultivation, so that the sweet corn farming business gets great results. Keywords : Income, Capital, farming experience, and level of education.